The films of Nick Deocampo : Beyond the mainstream - Lacuestra, Lolita R. (Pasig City, Philippines : Anvil Publications, 1997)
The film was made in the clandestine fashion best suited to deal with the repressive regime, which coerced every artist to conform to its dictates on media. I knew that if I had to make film, I had to make it different.
The films -- Oliver -- Children of the regime -- Revolutions happen like refrains in a song -- Ynang Bayan: to be a woman is to live at a time of war -- Memories of old manila -- Isaak -- The sex warriors and the samurai.
Keywords: MOTION PICTURES -- PHILIPPINES